Effect of Water Decoction of the Crown of God Fruit on the Reduction of Blood Pressure - Siswi Wulandari; Bram Mustiko; Putri Erika Kulistiyani; Pria Salsabila Ambar (Journal of Global Research in Public Health, 2021)
Background: Hypertension is a disease that often appears in developing countries such as Indonesia. A person is said to be hypertensive and at risk of health problems if after several measurements. The purpose of the study was to analyze the effect of boiling water on the decline of blood pressure in menopausal women with hypertension in Kediri City. Methods: This research is a pre design experiment, with a type of pre experimental type one group pre post test design. Sampling techniques using purposive sampling. With a population of 68 people and a sample used numbering 16 respondents. Data collection using observation sheets and research materials namely tensimeters. Results: In normality tests using Shapiro wilk blood pressure before and after being given boiling water of the mahkota dewa fruit obtained p value 0.03 and 0.41 while diastolic blood pressure before and after being given boiling water of the mahkota dewa fruit obtained p value 0.00 and 0.01. The results of data analysis using wilcoxon signed rank statistical test were obtained p-value result 0.00 with α level (0.05). Conclusion: The results showed there was an effect of boiling water of the mahkota dewa fruit on the decrease in blood pressure in menopausal women with hypertension. Researchers hope to increase the knowledge, skills of respondents as well as utilize the fruit in handling and treating hypertension.